Optimalisasi Customer Engagement Tvku Sebagai Strategi Komunikasi Pemasaran Di Era Digital - Nopianti, Elsa Sofi; Triyono, Agus (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to examine the marketing strategies implemented by TVKU (Television of Dian Nuswantoro University) in optimizing customer engagement in the digital era. As a local television station, TVKU faces significant challenges in maintaining its existence amidst the rapid growth of digital media. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation involving the TVKU marketing team and its business partners. The results show that TVKU applies three main marketing strategies: pull, push, and pass. The pull strategy is implemented by creating relevant, engaging, and educational content through digital platforms such as Instagram, YouTube, and TikTok. The push strategy involves partnerships with various parties, both commercially and through barter agreements, along with offering flexible promotional services. The pass strategy focuses on building a positive brand image through consistent content and sustainable collaborations. These strategies have proven effective in increasing audience involvement (customer engagement) and expanding the network of business partners. This research is expected to serve as a reference for local media companies in developing relevant marketing strategies in the digital age, and to contribute to the advancement of communication and digital marketing studies.